EVALUASI KEPUASAN DAN ANALISIS FAKTOR YANG MEMENGARUHI KEPUASAN MASYARAKAT TERHADAP PELAYANAN KEFARMASIAN OLEH APOTEKER DI APOTEK WILAYAH JAWA BARAT - Wira Dirgantara, Chua
Patient satisfaction is one of the important factors that determine the quality of a service provided by pharmacists and health facilities. The quality of service may be measured by examining the adequacy of performance with patient expectations for pharmaceutical services. This study was conducted to assess satisfaction and analyze factors that influence societies' satisfaction with pharmacy services provided by pharmacists at pharmacies in the West Java region. The research was conducted online by distributing surveys completed by 482 respondents who met the inclusion criteria. Primary data was obtained from the results of the distribution of Service Quality (SERVQUAL) questionnaires, which consist of 5 dimensions with 28 attributes. The questionnaires were already valid and reliable. The gap analysis was conducted using the SERVQUAL approach, Customer Satisfaction Index (CSI), and Importance-Performance Analysis (IPA). The level of satisfaction of pharmaceutical services by pharmacists at pharmacy in the West Java region was in the very satisfied category with a CSI value of 89.1%. Pharmaceutical performance has met respondents' expectations in all dimensions, but one of the attributes associated with the cleanliness of the pharmacy environment on the assurance dimension was still not as expected. The gap analysis on all dimensions showed a negative value which indicated the need to improve the performance of pharmacy services. In the IPA analysis, the attribute that needed to be the main priority for improvement was the cleanliness of the pharmaceutical environment.